Rectal prolapse in children: a study of 71 cases - Sarmast, Mohammad-Hossein; Askarpour, Shahnam; Peyvasteh, Mehran; Javaherizadeh, Hazhir; Mooghehi-Nezhad, Meisam (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction: Prolapse of the rectum is the herniation of the rectum through the anus, which may be categorised as mucosal or complete. Aim : To evaluate the clinical manifestation, treatment, and surgical complications of children with rectal prolapse over a 6-year period. Material and methods: This study was carried out on children aged < 14 years who were admitted or referred for rectal prolapse that failed to respond after medical treatment in Imam Khomeini and Abouzar Children’s Hospital. Duration of the study was 6 years starting in March 2002. These cases were referred after failure of medical and conservative treatment. Age, sex, clinical manifestation, and type of procedure were recorded. Analysis was done using SPSS version 11.0 (SPSS Inc, Chicago, IL, USA). The 2 test was used for comparison. Results: Seventy-one cases were included in this study. Of these cases, 50 (70.4%) were male and 21 (29.6%) were female (p < 0.0001). Mean age of cases was 4.97 ±3.42 years (range: 2 days to 13 years). Of the male cases, 38% were in the age range of 3–6 years. In female cases, 57.1% were in the range of 1.5–3 years. Of all 71 cases, injection sclerotherapy was done for 50 (70.43%) for the first time. Twenty-one cases had history of injection sclerotherapy and 16 (22.53%) were treated by perineal surgery, and 5 (7.04%) had abdominal surgery. One case experienced recurrent rectal prolapse (1.40%) following injection sclerotherapy. Conclusions : In girls, more than half of the cases were in the age range 1.5–3 years. Among male cases, 38% were in the age range of 1.5–3 years. The results of treatment of rectal prolapse in our hospitals was similar to that seen in developed countries.